The Impact of Infrastructure on Economic Growth in Central Java 2016-2020 - Rossani, Dhea Nabilla; Setyowati, Eni (Prosiding University Research Colloquium, 2022)
This research was conducted to analyze how much influence road infrastructure, education and health have on economic growth in Central Java Province in 2016-2020. Gross Regional Domestic Product (GDP) as the dependent variable, while road infrastructure, education, and health are independent variables. This research uses panel data regression analysis using the Eviews 10 program computer tool. This study uses secondary data obtained from the Central Statistics Agency for a period of 5 years starting from 2016-2020. The method used is a quantitative approach. The results showed that the road variable had a negative and significant effect on economic growth. The variables of education and health have a positive and significant influence on the economic growth of Central Java. The limitation of this research is that the researcher only takes three independent variables, namely road infrastructure, education infrastructure, and health infrastructure, while there are still other factors that cause the increase or decrease in economic growth in Central Java Province.